Gambaran Proses Grieving atas Kehilangan Anggota Keluarga Akibat Virus COVID-19 - Ida Ayu Putu Somawati; David Hizkia Tobing (Jurnal Pendidikan Indonesia, 2025)
The lost of family members caused by COVID-19 will result in deep anguish. The fact that other family members should self-isolate and the strict burial procedures are inhibitors for them to get involved in said burial, as a symbol of their last goodbyes. This article explains how a person grieves after the death of a family member because of COVID-19. Through the literature review, this article explains the definition of grieving, a person’s tasks in a mourning period, the loss of a family member and grieving in the COVID-19 era, burial without family members, and how to resolve continual grieving so that one may continue on living after going through the death of a family member because of COVID-19.